2022
DOI: 10.3390/e24121851
|View full text |Cite
|
Sign up to set email alerts
|

Exact Solution of a Time-Dependent Quantum Harmonic Oscillator with Two Frequency Jumps via the Lewis–Riesenfeld Dynamical Invariant Method

Abstract: Harmonic oscillators with multiple abrupt jumps in their frequencies have been investigated by several authors during the last decades. We investigate the dynamics of a quantum harmonic oscillator with initial frequency ω0, which undergoes a sudden jump to a frequency ω1 and, after a certain time interval, suddenly returns to its initial frequency. Using the Lewis–Riesenfeld method of dynamical invariants, we present expressions for the mean energy value, the mean number of excitations, and the transition prob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
2
4
0
Order By: Relevance
“…This is a direct consequence of equations (44) and (45). The equations (41)-( 45) generalize, for a generic intermediary frequency ω int (t) and a final frequency ω f , the results found in [61] for the particular case where ω int (t) = ω 1 and ω f = ω 0 .…”
Section: Squeezing Parameter and Related Quantities For T > τsupporting
confidence: 56%
See 2 more Smart Citations
“…This is a direct consequence of equations (44) and (45). The equations (41)-( 45) generalize, for a generic intermediary frequency ω int (t) and a final frequency ω f , the results found in [61] for the particular case where ω int (t) = ω 1 and ω f = ω 0 .…”
Section: Squeezing Parameter and Related Quantities For T > τsupporting
confidence: 56%
“…, even when the initial and final frequencies are the same (ω f = ω 0 ) [61]. The argument is similar for ( )…”
Section: Squeezing Parameter and Related Quantities For T > τmentioning
confidence: 60%
See 1 more Smart Citation
“…In ref. [40], it has been shown that for the particular case 25), one can obtain the effective evolution as…”
Section: The Lewis-riesenfeld Approach and The Ermakov Equationmentioning
confidence: 99%
“…Existing theoretical literature on driven harmonic oscillators using a Lie algebraic approach often focus on abrupt or adiabatic changes in the parameters of the system in order to approximate its dynamics taking advantage of time-independent solutions [23][24][25][26]. We are interested in the time-dependent driven QHO from a Lie theory point of view that provides a framework to optimize state engineering at any given rate of change without resorting to approximations.…”
Section: Introductionmentioning
confidence: 99%